Historico-cultural recontextualization in translating ancient classics: a case study of Gopal Sukhu's The Songs of Chu. (4th March 2022) - Tian, Chuanmao; Wang, Xu; Xu, Mingwu
ABSTRACT: Adequate historico-cultural recontextualization promotes the reception and transmission of translations of ancient classics, highlighting the importance of translators' recontextualization of ancient classics in target texts. Combining thick translation and paratextual theory, we first propose a theoretical model for recontextualizing ancient classics. Then, we summarize cultural recontextualization approaches and the use of paratexts as recontextualizing strategies via a case study of Gopal Sukhu's translation of the Chuci (楚辞), a classic of ancient Chinese literature. Finally, we compare translations by Sukhu and others to explore the strengths of Sukhu's version, delineating implications for ancient classics translation more generally. We then offer two significant conclusions. Firstly, translators recontextualize source texts through various paratexts, including introduction, note, appendix, and index, in order to remove historico-culturally related reading barriers, helping readers develop a thorough understanding of the source text. Secondly, a multimodal approach combining research and translation benefits the reader by rendering ancient classics accessible through thick translations rich with paratexts.